2014
DOI: 10.1063/1.4895511
|View full text |Cite
|
Sign up to set email alerts
|

Near-interface charged dislocations in AlGaN/GaN bilayer heterostructures

Abstract: Understanding the behavior of semiconductor dislocation defects in AlGaN/GaN heterostructures is necessary in order to produce powerful and efficient transistors. This letter presents a straightforward technique to characterize dislocation defects with charges along their loops in a bilayer system. This is important regarding the behavior of near-interface dislocations in order to obtain an insight of the mechanical and physical responses. We characterize piezoelectric polarization and emphasize on the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…11. The orientation of threading dislocation lines along direction has also been experimentally observed for grown epitaxial GaN layers [34]. The best linear fit of the two data sets of Fig.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…11. The orientation of threading dislocation lines along direction has also been experimentally observed for grown epitaxial GaN layers [34]. The best linear fit of the two data sets of Fig.…”
Section: Resultssupporting
confidence: 53%
“…The internal stress due to the lattice mismatch is the main cause of the formation of misfit dislocations. Threading dislocations, however, are generated as a result of the coalescence of adjacent grains during epitaxial growth at high temperatures with a density ranging between 10 8 and 10 11 cm −2 [34]. Furthermore, it has been demonstrated that the most dislocations in AlGaN/GaN heterostructures are of threading straight type [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the built-in electric field in AlN/GaN/AlN heterostructures enhances the electron–phonon interaction via the deformation potential and the piezoelectric potential. In our samples, when the nanopits diameter is increased, the built-in electric field is expected to rise due to increasing defect density 4 , 37 …”
Section: Resultsmentioning
confidence: 96%
“…These nanopits are commonly observed in III-nitride heterostructures and associated with misfit and threading dislocation terminus 35 , 36 . While threading dislocations are generated through the coalescence of adjacent grains during growth, misfit dislocations are formed due to the internal stress caused by the lattice mismatch between the (Al)GaN layer and the substrate 37 . Misfit and threading dislocations can be entangled with each other during growth to form closed or open dislocation loops that prolong toward the top surface of the epitaxial layer.…”
Section: Resultsmentioning
confidence: 99%